1993
DOI: 10.1084/jem.178.4.1175
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor cell hyperplasia with rare development of myeloid leukemia in interleukin 11 bone marrow chimeras.

Abstract: Post 5-fluorouracil-treated murine bone marrow cells infected with a recombinant retrovirus (murine stem cell virus-interleukin 11 [MSCV-IL-11]) bearing a human IL-11 gene were transplanted into lethally irradiated syngeneic mice. Analysis of proviral integration sites in DNA prepared from hematopoietic tissues and purified cell populations of long-term reconstituted primary and secondary recipients demonstrated polyclonal engraftment by multipotential stem cells. High levels (100-1,500 U/ml) of IL-11 were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…The murine IL-3-dependent bone marrow DN2mt progenitor [17,21,28], PGMD1 [36] and M-NSF-60 (ATCC No. CRL-1838; American Type Culture Collection, Manassas, VA) cell lines were routinely maintained in Iscove’s Modified Dulbecco’s Medium (IMDM; Mediatech Inc., Herndon, VA) containing 4 mM L-glutamine, 50 IU/ml penicillin, 50 μg/ml streptomycin, 10% heat-inactivated fetal bovine serum (FBS, Cambrex BioScience Walkersville, Inc., Walkersville, MD), 10% conditioned medium from X630-rlL3 cells (a source of recombinant IL-3) plus/minus 0.75 mg/ml geneticin (Invitrogen Corp., Carlsbad, CA) as applicable.…”
Section: Methodsmentioning
confidence: 99%
“…The murine IL-3-dependent bone marrow DN2mt progenitor [17,21,28], PGMD1 [36] and M-NSF-60 (ATCC No. CRL-1838; American Type Culture Collection, Manassas, VA) cell lines were routinely maintained in Iscove’s Modified Dulbecco’s Medium (IMDM; Mediatech Inc., Herndon, VA) containing 4 mM L-glutamine, 50 IU/ml penicillin, 50 μg/ml streptomycin, 10% heat-inactivated fetal bovine serum (FBS, Cambrex BioScience Walkersville, Inc., Walkersville, MD), 10% conditioned medium from X630-rlL3 cells (a source of recombinant IL-3) plus/minus 0.75 mg/ml geneticin (Invitrogen Corp., Carlsbad, CA) as applicable.…”
Section: Methodsmentioning
confidence: 99%
“…NEUMEGAO has been shown to increase blood platelet counts when administered in vivo as a single agent to nonmyelosuppressed rodents, dogs and nonhuman primates. Moreover, thrombocytosis and hematopoietic progenitor cell hyperplasia were observed in lethally irradiated mice transplanted with mouse bone marrow cells that had been retrovirally transfected with the human (h) IL-11 gene [48].…”
Section: Preclinical Rationale For Use Of Neumega~ To Treat Chemothermentioning
confidence: 99%
“…NEUMEGA@ has had either no effect or minor and inconsistent effects on the growth of myeloma cells [52,53] and did not reverse steroid-induced growth arrest in three human myeloma cell lines [54]. NEUMEGAO has no direct effect on acute myelogenous leukemia (AML) cells but has been shown to augment the proliferation of at least some AML cells stimulated by other cytokines [55, 561. In the study by Huwley et al [48], cells from one secondarily transplanted pedigree showed a leukemic phenotype, and a transformed cell line expressing the IL-11 gene was produced from one quarternarily transplanted animal [48]. This cell line was dependent on LL-3 for continuous growth in vitro, and the cells differentiated into mature leukocytes in vitro in response to GM-CSF treatment.…”
Section: Preclinical Rationale For Use Of Neumega~ To Treat Chemothermentioning
confidence: 99%
“…The transplantation of BM cells was performed as previously described. 19,20 In brief, BM was flushed from the hind limbs of donor mice that had been injected 4 days previously with 150 mg/kg 5-flurorouracil (Roche, Laval, QB) in phosphate-buffered saline (PBS). Following erythrocyte lysis, nucleated cells were cultured in 100-mm dishes at a density of 5 ϫ 10 5 cells/mL in prestimulation medium (Iscoves modified Dulbecco medium [IMDM]; Life Technologies), 10% fetal calf serum (FCS; Life Technologies), 1% penicillin/streptomycin (Life Technologies), 2 mM glutamine (Life Technologies), 50 M 2-mercaptoethanol (2-ME) supplemented with 10% conditioned medium from X630-rIL3 cells, 21 10% conditioned medium from Sp2/mIL6 cells, 22 and 2% to 5% conditioned medium from Sp2/soluble Flt3 ligand (sFLt3L) for 2 days.…”
Section: Transduction Of Bm Precursors and Transplantationmentioning
confidence: 99%